Mirrors of salt : proceedings of the First International Congress on the Anthropology of Salt : 20-24 August 2015, 'Al. I. Cuza' University, Iași, Romania - Alexianu, Marius; Curcă, Roxana-Gabriela; Weller, Olivier; Dumas, Ashley A. (Archaeopress Archaeology, 2023)
'Mirrors of Salt' publishes the proceedings of the First International Congress on the Anthropology of Salt, which took place at the Alexandru Ioan Cuza University in Iași (Romania).